Review of the calculation of DC-link capacitor current - Guo, Cheng; Xin, Ziyue; Han, Jing; Hu, Liangdeng; Lu, Bin (Frontiers in Energy Research, 2023)
In the voltage source power electronic converter, DC-link capacitors usually work as buffering elements between the DC and AC sides. The high failure rate and large space occupied by the DC-link capacitors will directly affect the reliability and power density of the converters. The analysis and calculation of DC-link capacitors current is crucial for the achievement of refined design of converters. In this paper, the analysis and calculation methods of DC-link capacitors current are divided into three categories according to the calculation principle: simulation method, RMS analysis method and spectral analysis method, and their calculation methods are summarized. Firstly, the types of capacitors and their characteristics are briefly introduced. Secondly, the three-phase two-level converter is taken as an example to introduce the basic principles, calculation steps, application scope, advantages and disadvantages of the latter two methods in detail, as well as the influence of non-ideal factors such as output ripple on the calculation results. This paper also discusses the calculation of multi-level converter's DC-link capacitors current spectrum and the current characteristics of multi-phase converters, which is rarely reported. Thirdly, the problem of resonance between the DC-link capacitors and the dc bus inductor is introduced. For the distributed arrangement of multiple DC-link capacitors on dc bus converters, this paper proposes a method based on a constant current source equivalent circuit, which can accurately calculate the DC-link capacitors current spectrum that effects by loop current and resonance. Finally, the current problems and future directions of DC-link capacitors design are pointed out.